Upaya Pencegahan Infeksi Saluran Kemih Melalui Pemeriksaan Urinalisis pada Populasi Lansia di Panti Werdha Hana - S, Donatila Mano; Santoso, Alexander Halim; Gunaidi, Farell Christian; Alexin, Corry Calista; Evelyn Evelyn (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
Urinary tract infections (UTIs) are common health problems among the elderly and can significantly reduce quality of life due to complications such as systemic infections, kidney disorders, and recurrent infections. Older adults often do not recognize early symptoms of UTIs, as the manifestations are atypical and frequently mistaken as part of the normal aging process. The Community Service Program (PKM) conducted at Panti Werdha Hana aimed to increase elderly awareness of the importance of early UTI detection through urinalysis as a screening method. This activity was carried out using the Plan-Do-Check-Act (PDCA) approach, which included urine testing for leukocyte esterase, nitrites, and protein, as well as educational sessions on UTI risk factors and prevention strategies. Among the 76 participants examined, 2 individuals (3.08%) tested positive for leukocyte esterase and 1 individual (1.54%) tested positive for nitrites, indicating potential infection. These findings suggest that simple urin tests can serve as an effective initial step in detecting UTIs early and promoting timely interventions to maintain urinary tract health and improve the overall quality of life in the elderly.